Discrete-time signal processing. - Oppenheim, Alan Victor, 1937-; Schafer, Ronald W., 1938- (Upper Saddle River : Pearson, 2010)
THE definitive, authoritative text on DSP - ideal for those with an introductory-level knowledge of signals and systems. Written by prominent DSP pioneers, it provides thorough treatment of the fundamental theorems and properties of discrete-time linear systems, filtering, sampling, and discrete-time Fourier Analysis. By focusing on the general and universal concepts in discrete-time signal processing, it remains vital and relevant to the new challenges arising in the field.